Subcutaneous Metastasis of Atypical Meningioma: Case Report and Literature Review - Liu, Yikui; Li, Jian; Duan, Yu; Ye, Yao; Xiao, Li; Mao, Renling (World neurosurgery, 2020)
Meningioma, a neoplasm of the meninges, is usually a benign localized tumor. Extraneural metastasis is an extremely rare complication of meningiomas, and only a few cases have been reported to date. The present study reports a case of scalp metastasis of an atypical meningioma and discusses the types of atypical meningiomas and their management options. A 69-year-old man presented with scalp metastasis of an atypical meningioma. Six years after the right frontoparietal meningioma lesion was completely resected, an isolated subcutaneous metastasis developed at the right frontal region of the scalp, originating at the scar left by the first surgery. Postoperative histologic examination of the subcutaneous tumor revealed the features of an atypical meningioma. This study highlights that resection of meningiomas is still associated with a risk of iatrogenic metastasis. Surgeons should carefully wash out the operative field and change surgical tools frequently to avoid the potential risk of metastasis.